Genomic signatures of adaptation in seed traits in the wild plant Brassica incana - Lucrezia Laccetti; Angelino Carta; Maria Rosaria Barone Lumaga; Léa Frachon; Giovanni Scopece (Communications Biology)
Abstract Seed traits underlying germination, by determining the environment experienced by plants throughout their lifetime, can play a key role in shaping plants’ adaptive strategies. However, the genomic bases of adaptation in seed traits and its link with local biotic and abiotic environments remain largely unexplored. Here, we used a pool-sequencing approach combining genome-wide association (GWA), genome-environment association (GEA) and a genome wide scan of a spatial genomic differentiation index (XTX) to identify putative signatures of adaptation in seed traits and to climate and pollinator community across 14 populations of the wild plant species Brassica incana. We observed a complex genetic architecture potentially involved in seed trait adaptation, which varied depending on the seed trait function. Also, we identified several candidate genes simultaneously linked to signals of adaptation in seed traits and local abiotic or biotic conditions. These results expand our understanding on the adaptive value of seed traits, on its interaction with environmental conditions and on its potential for shaping the evolutionary trajectory of wild plant populations.